COUNTERING THE JUDICIAL MAFIA FROM THE POLITICAL PERSPECTIVE OF NATIONAL LAW - Tantimin Tantimin (MIZAN, Jurnal Ilmu Hukum, 2022)
Judicial mafia is a crime of abuse of office or can be said to be a dirty game in law enforcement and involves law enforcement officials. From the political aspect of national/criminal law, the judicial mafia can be an abuse of office that causes a violation of the law. The policy of developing the justice system is defined as a reasonable effort to develop and improve its quality. The effort to eradicate the judicial mafia is essentially to restore public trust and respect for the judicial system. The purpose of this study is to analyze and describe the efforts to overcome the judicial mafia in law enforcement and review the law enforcement process carried out by law enforcement officers in achieving justice. This research uses normative legal research methods. The data is based on secondary data obtained from library sources or legislation. This study shows that overcoming the judicial mafia requires a policy in the development of the justice system, which is defined as part of reasonable efforts to develop and improve the quality of the justice system. The effort to eradicate the judicial mafia is essentially an effort to restore public trust and respect in the judicial system.